Mobile-Optimized AI-Driven Personalized Learning: A Case Study at Mohammed VI Polytechnic University - Baba, Khalid; El Faddouli, Nour-Eddine; Cheimanoff, Nicolas (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the rise of mobile learning platforms, it has become increasingly evident that individuals require personalized experiences that are tailored to the strengths and limitations of mobile devices. The present study explores the significant impact that personalized mobile learning environments, powered by artificial intelligence (AI), could have. This study specifically evaluates the impact of an AI-driven personalized educational platform, designed for mobile devices, on the academic achievement and educational progress of students at Mohammed VI Polytechnic University. The platform, designed for mobile devices, allows instructors to easily upload information. Learners can interact with an AI mentor through a chat interface that is seamlessly integrated into their mobile course materials. The system, constructed using cutting-edge technologies such as Langchain, Pinecone, and the LLM Model, excels at providing personalized, real-time feedback and support for learners who are frequently mobile. This study compared two groups of students. One group had access to a mobile personalized learning platform powered by AI, whereas the control group did not have access to it. We conducted a comparative analysis of mobile educational experiences, levels of engagement, and academic outcomes across these groups. In addition, qualitative feedback was gathered from educators and students to evaluate the mobile usability and effectiveness of the system. The results of our study demonstrate that the AI-driven mobile-tailored learning system significantly improves the experience of mobile learners. The increased levels of engagement, improved understanding, and superior academic achievements support our claim. This study not only supports the potential of AI-driven personalized mobile learning in higher education but also emphasizes the importance of continuous innovation to improve its usefulness and effectiveness.